Pengaruh Tax Planning, Struktur Modal, Keputusan Investasi, dan Profitabilitas terhadap Nilai Perusahaan - Debyla Ayu Wardana; Hestin Sri Widiawati; Mar’atus Solikah (BADAN PENERBIT STIEPARI PRESS, 2025)
This research is based on the importance of company value as an indicator of success, competitiveness, and future growth potential. Company value is measured using the Price to Book Value (PBV) ratio, which reflects the comparison between market value and book value of equity. The independent variables in this study include tax planning, capital structure, investment decisions, and profitability. Tax planning is measured by the Tax Retention Rate (TRR), capital structure is measured by the Debt to Equity Ratio (DER), investment decisions are measured by the Price Earning Ratio (PER), and profitability is measured by Return on Equity (ROE). This study aims to analyze the partial and simultaneous effects of these four variables on company value in the financial services sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research approach used is quantitative with multiple linear regression analysis methods. The study population consisted of 105 financial services companies listed on the IDX, and through purposive sampling techniques, 11 companies were obtained as samples. The data used are secondary data sourced from annual financial reports, and processed using SPSS software version 27. The results of the study indicate that partially, tax planning does not have a significant effect on firm value, which indicates that tax efficiency efforts are not always directly reflected in an increase in the company's market value. In contrast, capital structure, investment decisions, and profitability are proven to have a significant effect on firm value, which indicates that funding policies, investment strategies, and financial performance have an important role in increasing investor confidence. Simultaneously, the four independent variables have a significant effect on firm value. These findings contribute to the development of financial management theory, particularly in the context of the financial services sector in Indonesia, and offer practical implications for company management and investors in formulating optimal strategies to maximize firm value.